Regime-building democratization and international administration - d (Oxford : Oxford University Press, 2009)
A study of regime change in the context of international administration, this text highlights 'regime-building' practices, as well as examining the aims and influences of international administrations in the area of democratic development.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Democratization -- International cooperation; Regime change -- Kosovo (Republic); Regime change -- Bosnia and Hercegovina; Regime change -- East Timor